2009
DOI: 10.4049/jimmunol.0803424
|View full text |Cite
|
Sign up to set email alerts
|

The Microenvironment of Germ Cell Tumors Harbors a Prominent Antigen-Driven Humoral Response

Abstract: Germ cell tumors are a heterogeneous group of neoplasms derived from residual primordial tissue. These tumors are commonly found in the brain, testes, or ovaries, where they are termed germinomas, seminomas, or dysgerminomas, respectively. Like several other tumor types, germ cell tumors often harbor an immune cell infiltrate that can include substantial numbers of B cells. Yet little is known about whether the humoral immune response affects germ cell tumor biology. To gain a deeper understanding of the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 33 publications
(31 reference statements)
4
53
0
Order By: Relevance
“…It has also been reported that the infiltrating B cells in different types of cancers are clonal and express immunoglobulins that originate from a dominant germ line gene (47)(48)(49). Here, a tumor antigen, as opposed to a transplantation antigen, may drive the infiltrating cells and possibly tumor-specific mechanisms of local "immunosuppression" are also operant.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the infiltrating B cells in different types of cancers are clonal and express immunoglobulins that originate from a dominant germ line gene (47)(48)(49). Here, a tumor antigen, as opposed to a transplantation antigen, may drive the infiltrating cells and possibly tumor-specific mechanisms of local "immunosuppression" are also operant.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is therefore surprising that ELFs arise in tumours at all. However, ELFs have been described in numerous cancers including colorectal,60, 88 rectal,89 breast,67, 90, 91 ovarian67, 92 and germ cell93 cancers, as well as melanoma,62, 67, 94 mucosal‐associated lymphoid tissue lymphoma39 and non‐small cell lung carcinoma95, 96 (NSCLC; see Dieu‐Nosjean et al . for a comprehensive review of ELFs in cancer9).…”
Section: Elfs As Regulators Of Anti‐tumour Immunitymentioning
confidence: 99%
“…In these tumors, molecular characterization of Ig gene rearrangements showed that clonal proliferation, somatic Ig mutation, and clonal selection all occurred (24)(25)(26). The analysis of primary germ cell cancers has revealed the presence of lymphoid follicles with germinal centers, in which ongoing antigen-driven antibody responses occurred (27). Finally, ectopic lymphoid structures have been detected in colorectal cancer, with their presence being correlated to a better prognosis (28).…”
Section: Introductionmentioning
confidence: 99%